Influencia del abandono familiar en la deficiente atención de las personas con habilidades diferentes en el C.E.B.E. Chepén: 2018. - Sanchez Hernandez, Helen Melissa (2019)
The main purpose of this study is to analyze the influence of family abandonment on the deficient attention of people with different abilities in the C.E.B.E. Chepén: 2018. The type of applied research has been considered, based on a descriptive design, and the sample consisted of 45 people with different skills, with which we worked applying the methods and techniques of quantitative research: Statistical method and as a technique to the survey, and qualitative research: Inductive - deductive method; and as techniques direct observation and interview. Finally, we consider that this research is a starting point to persuade public officials and businessmen that we must work in concert to implement the policy of social inclusion to all people with disabilities to improve their quality of life. The present thesis is subdivided into: Chapter I. Introduction: Problematic reality, antecedents, theoretical bases and conceptual framework; Chapter II. Methodology; Chapter III. Results presentation; Chapter IV. Discussion of results. Chapter V. Conclusions; Chapter VI. Recommendations, Chapter II. Bibliographic references and Annexes.